ISOLATION AND CHARACTERIZATION OF NOVEL MICROSATELLITE LOCI IN GREEN TIGER SHRIMP (PENAEUS SEMISULCATUS): Life Sciences-Genetics - OTHMAN, AHMAD SOFIMAN; JAHROMI, SAEID TAMADONI (International Journal of Life Science and Pharma Research, 2011)
The green tiger shrimp (Penaeus semisulcatus) is an economically important species among native Iranian Shrimps. Microsatellite loci were developed for population genetic assessment of this species in Iranian waters. A total of eight polymorphic microsatellite loci were developed and tested on 40 individuals. The number of alleles per locus ranged from 5 to 12 with average of 7.38 per locus. The values of the observed and expected heterozygosities ranged from 0.100 to 0.800 and 0.534 to 0.869 respectively. These novel microsatellite markers provide useful tools to assess genetic variation and genetic structure in the populations of P. semisulcatus to facilitate a selective breeding program.